Medrano Sánchez, María Isabel; Mamani Salinas, Alfredo; Muñoz Ccuro, Felipa Elvira; Diaz Bazán, Ricardo Alfredo; Medrano Sánchez, Emilio José. The majestic Lake Titicaca and the cities' domestic wastewater treatment plants that surround it. Sector-Peru. E - Peruana de Derecho Internacional, Sociedad (2020)
Sector-Peru. Edition 2020, 1st Ed., Pp 116.